Word class effect on visual asymmetry - P.G, Radhika (Journal of All India Institute of Speech and Hearing)
Research on the visual asymmetries for word class (abstractors concrete norms) have been done in the alphabetic and ideographic script, i.e., English and Kanji respectively. The general finding has beenthat the RVF/LH shows an advantage over the LVF in processing the abstract norms. The LVH/RH processes the concrete norms. This study aimed to (1) Test if there is a RVF/LH advantage for abstract words, (2) Test if there is a LVF/RH advantage for concrete words, for Kannada.